Laser additive manufacturing bulk graphene–copper nanocomposites. (6th October 2017) - Hu, Zengrong; Chen, Feng; Lin, Dong; Nian, Qiong; Parandoush, Pedram; Zhu, Xing; Shao, Zhuqiang; Cheng, Gary J
Abstract: The exceptional mechanical properties of graphene make it an ideal nanofiller for reinforcing metal matrix composites (MMCs). In this work, graphene–copper (Gr–Cu) nanocomposites have been fabricated by a laser additive manufacturing process. Transmission electron microscopy (TEM), x-ray diffraction (XRD) and Raman spectroscopy were utilized to characterize the fabricated nanocomposites. The XRD, Raman spectroscopy, energy dispersive spectroscopy and TEM results demonstrated the feasibility of laser additive manufacturing of Gr–Cu nanocomposites. The microstructures were characterized by high resolution TEM and the results further revealed the interface between the copper matrix and graphene. With the addition of graphene, the mechanical properties of the composites were enhanced significantly. Nanoindentation tests showed that the average modulus value and hardness of the composites were 118.9 GPa and 3 GPa respectively; 17.6% and 50% increases were achieved compared with pure copper, respectively. This work demonstrates a new way to manufacture graphene copper nanocomposites with ultra-strong mechanical properties and provides alternatives for applications in electrical and thermal conductors.